The influence of stigma and disability acceptance on psychosocial adaptation in patients with stoma: A multicenter cross-sectional study - Xi, Zhang; Rong, Chen M.; Ling, Lin J.; Hua, Zeng P.; Rui, Gao; Fang, Huang G.; Long, Wang; Zhen, Zhuo H.; Hong, Li (Frontiers in Psychology, 2022)
Background: The stoma can cause serious physical and psychological distress to the patient, leading to an inability to live a normal life; although it effectively improves the 5-year survival rate of patients. The purpose of this study is to explore the status of stigma and disability acceptance of patients with stomaand their influences on psychosocial adaptation.. Methods: A total of 259 patients with stoma in 6 hospitals were enrolled. And this research adhered to the STROBE guideline. The ostomy adjustment inventory-20、acceptance of disability scale and social impact scale were used to collect data. The hypothetical path model was tested using the SPSS version 22.0 software and AMOS version 26.0 software. Results: stigma、disability acceptance and psychosocial adaptation was associated. The sense of stigma was severe , the acceptance of disability was medium and the psychosocial adaptation was poor. Also, The hypothesis model of this study fitted the data well, and the results showed that disability acceptance positively affected psychosocial adaptation; while stigma negatively affected psychosocial adaptation, and disability acceptance mediated between stigma and psychosocial adaptation. Conclusion: The stigma and disability acceptance of patients with stoma are serious problems that are closely related to their psychosocial adaptation. Medical staff should take some interventions based on different paths to reduce stoma patients' stigma and guide them to improve disability acceptance, thus to improve the level of psychosocial adaptation of patients with stoma. Keywords: Stoma; Stigma; Disability Acceptance; Psychosocial Adaptation; Structural Equation Model；